Sterols Have Higher Affinity for Sphingomyelin than for Phosphatidylcholine Bilayers even at Equal Acyl-Chain Order - Lönnfors, Max; Doux, Jacques P.F.; Killian, J. Antoinette; Nyholm, Thomas K.M.; Slotte, J. Peter (Biophysical journal, 2011)
The interaction between cholesterol and phospholipids in bilayer membranes is important for the formation and maintenance of membrane structure and function. However, cholesterol does not interact favorably with all types of phospholipids and, for example, prefers more ordered sphingomyelins (SMs) over phosphatidylcholines (PCs). The reason for this preference is not clear. Here we have studied whether acyl-chain order could be responsible for the preferred sterol interaction with SMs. Acyl-chain order was deduced from diphenylhexatriene anisotropy and from the deuterium order parameter obtained by 2H-NMR on bilayers made from either 14:0/14:0(d27)-PC, or 14:0(d27)-SM. Sterol/phospholipid interaction was determined from sterol bilayer partitioning. Cholestatrienol (CTL) was used as a fluorescence probe for cholesterol, because its relative membrane partitioning is similar to cholesterol. When CTL was allowed to reach equilibrium partitioning between cyclodextrins and unilamellar vesicles made from either 14:0/14:0-PC or 14:0-SM, the molar-fraction partitioning coefficient (Kx) was approximately twofold higher for SM bilayers than for PC bilayers. This was even the case when the temperature in the SM samples was raised to achieve equal acyl-chain order, as determined from 1,6-diphenyl-1,3,5-hexatriene (DPH) anisotropy and the deuterium order parameter. Although the Kx did increase with acyl-chain order, the higher Kx for SM bilayers was always evident. At equal acyl-chain order parameter (DPH anisotropy), the Kx was also higher for 14:0-SM bilayers than for bilayers made from either 14:0/15:0-PC or 15:0-/14:0-PC, suggesting that minor differences in chain length or molecular asymmetry are not responsible for the difference in Kx. We conclude that acyl-chain order affects the bilayer affinity of CTL (and thus cholesterol), but that it is not the cause for the preferred affinity of sterols for SMs over matched PCs. Instead, it is likely that the interfacial properties of SMs influence and stabilize interactions with sterols in bilayer membranes.